2020
DOI: 10.1186/s12933-020-01036-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 2 diabetes mellitus on mid-term mortality for hypertrophic cardiomyopathy patients who underwent septal myectomy

Abstract: Background: Type 2 diabetes mellitus is common in cardiovascular disease. It is associated with adverse clinical outcomes for patients who had undergone coronary artery bypass and valve operations. The aim of this study was to evaluate the impact of type 2 diabetes mellitus on the midterm outcomes of patients with hypertrophic cardiomyopathy who underwent septal myectomy. Methods: We retrospectively analyzed the data of 67 hypertrophic cardiomyopathy patients with type 2 diabetes mellitus who underwent septal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…Our data reinforce data from previous studies demonstrating that T2DM was associated with poorer outcomes in patients with HCM [ 10 - 13 ]. For example, a study in 2022 by Lee et al [ 11 ] analyzed adverse outcome risk between HCM patients with and without T2DM using data from the Korean National Health Insurance Service database.…”
Section: Discussionsupporting
confidence: 92%
“…Our data reinforce data from previous studies demonstrating that T2DM was associated with poorer outcomes in patients with HCM [ 10 - 13 ]. For example, a study in 2022 by Lee et al [ 11 ] analyzed adverse outcome risk between HCM patients with and without T2DM using data from the Korean National Health Insurance Service database.…”
Section: Discussionsupporting
confidence: 92%
“…Comorbid medical conditions are important contributors to the development of arrhythmias in non-HCM cardiac conditions, [1][2][3][4][5][6][7] and while obesity and other comorbidities in HCM have been linked to heart failure progression, [15][16][17][18][19][20][21] We found no evidence that obesity or other comorbidities impact risk for SCD in HCM. Indeed, HCM patients with SCD events were younger, had similar BMI, and were less likely to have diabetes, hypertension, or hyperlipidemia than HCM patients without such events.…”
Section: Discussioncontrasting
confidence: 58%
“…8,9 More recently, obesity and other comorbidities have been demonstrated to impact clinical course in HCM, primarily via their impact on outflow obstruction and progressive heart failure. [15][16][17][18][19][20][21] However, whether such comorbidities affect development of clinically relevant arrhythmias in HCM remains unresolved. Therefore, we have taken the opportunity to evaluate the potential impact of obesity and other comorbidities on development of AF and SCD events in a large consecutive cohort of HCM patients.…”
mentioning
confidence: 99%
“…However, the difference in mortality was only significant in the last 5 years of the 15-year follow-up; the first 5 years of the study showed lower mortality in the presence of diabetes, which is concordant with our results. Another study looking at outcomes after septal myectomy in 201 HCM patients and comparing diabetes versus non-diabetes patients found identical mortality in both groups (Wang et al, 2020). Analysis of the OPTIMIZE-HF registry found that diabetes did not affect in-hospital mortality (Greenberg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%